The Internet of Things in Healthcare: Innovations and Challenges in Precision Diagnostics Systematic Review - Meshari Shaya Mubarak Alghabsah; Saud Ali Yahya Sayyad; Nasser Jerman D Almutairi; Emad Duhaim Mutlaq Almutairi; Zaben Allah Ali Nasser Alkorbi; Ahmed Hazza Ahmed Alshamrani; Thabet Mohammed Habib Alqahtani (International Journal of Medical Toxicology and Legal Medicine, 2024)
The rapid evolution of information technologies characterizes this digital age, the mobile advancement of the smartphone industry, the rising trend of multi-omic technologies, and the availability of the 5 G network and the significant data era. By embedding the knowledge needed for detection and actionable intelligence into intelligent sensors, querying devices, digital imaging and smartphone-based diagnostic assay tools, and interconnected networked intelligence, diagnostics are poised to become more innovative and more accurate. Notably, the Internet of Things has had an immense impact on multiple sectors ranging from digital imaging, intelligent sensing, digital diagnostics, digital biotechnology, telemedicine, precision agriculture, point-of-care testing, smart home systems, city planning, intelligent retail, and automated R&D. Implementing IoT technology in diagnostics and healthcare can help deliver personalized medical care specific to individual needs and facilitate more extensive remote healthcare, and management. This review investigates digital diagnostics' theoretical and technological progress through IoT technology. It also highlights the prospects and challenges of IoT in developing diagnostic applications. Through all of this theoretical integration, IoT-based tools like diagnostic, sensing, and imaging devices can provide high levels of automation and accuracy that have never before been seen in diagnostic processes, with the potential to act as a catalyst for a broader transformation in biomedicine and e-healthcare.